Arginine promotes fluoride uptake into artificial carious lesions in vitro. (March 2015) - Cheng, X; Xu, P; Zhou, X; Deng, M; Cheng, L; Li, M; Li, Y; Xu, X
Abstract Background This study focused on the interaction of arginine and fluoride on the remineralization of artificial enamel carious lesions in vitro. Methods Human enamel blocks with artificial carious lesions were prepared and randomly divided into six treatment groups (n = 30 for each group): deionized water, arginine solution, NaF solution, arginine/NaF solution, arginine‐free fluoride toothpaste slurry and arginine‐containing fluoride toothpaste slurry. After a pH‐cycling regimen for 10 days, subsets of specimens from each group were subjected to independent analysis, including surface microhardness (n = 8/30), cross‐sectional microhardness (n = 8/30), enamel fluoride uptake (n = 8/30) and polarized light microscopy (n = 6/30). The samples tested for surface microhardness were further subjected to simulated plaque acid challenge before surface microhardness was remeasured. Results Arginine solution promoted remineralization compared with deionized water control (p < 0.05). When used in combination with fluoride, arginine significantly increased fluoride uptake compared with fluoride alone (p < 0.05). In addition, lesions treated with arginine‐containing toothpaste also showed superior fluoride uptake compared with those treated with conventional fluoride toothpaste (p < 0.05). Conclusions Arginine promoted enamel fluoride uptake when used in combination with fluoride, thereby contributing to resistance of enamel to carious demineralization.